Original hospital lobby (1930)
An early photograph of the original lobby of Duke Hospital. A number of children are gathered with other patients. The two-sided desk can be seen in the center of the room. The two-sided desk has a long history at Duke. In 1934, Thomas D. Kinney, a medical student, sat at the desk during his evening work in the foyer of Duke Hospital directing patients for emergency treatment. When the desk was moved from the hospital to a storage area, the Kinney family asked if they could buy it. Dean Barnes Woodhall refused, but offered them the chance to store it and arrange for its restoration. The Kinneys made a study of the desk's construction period, the hardware and motifs, and ultimately restored the piece. A company was chosen to refinish the wood. When the black oil cloth was removed from the top surface, there in the middle was an 8 x 12 inch copper plate engraved with the following inscription: This desk was presented to Duke Hospital by Dr. William John Dann in March, 1938. It was formerly the property of the Reverend Henry Montagu Butler, D.D., headmaster of Harrow School (1859-1885), dean of Gloucester (1885-1886); master of Trinity College, Cambridge (1886-1918); and vice chancellor of Cambridge University (1889-1890). He used this desk at Harrow and later in his study in the Master's Lodge, Trinity College. The desk currently resides in the Medical Center Library.